An owal from the Paleocene of Walbeck, Germany - G. Mayr (Fossil Record, 2002)
An owl of the genus Berruornis is described from a Paleocene fissure filling of Walbeck, Germany. The specimen is a well preserved incomplete right tarsometatarsus and is the earliest Old World record of an owl. A praemaxilla from the same locality which comes from a similarly-sized raptorial bird is described and is clearly distinguished from the praemaxilla of all extant raptorial birds. Although it might also belong to Berruornis, the specimen is classified as Aves incertae sedis in this study. Despite the fact that the Walbeck material was discovered more than 60 years ago, these two specimens are the first bird bones to be described from the numerous avian remains found at this locality. Eine Eule der Gattung Berruornis wird aus einer paläozänen Spaltenfüllung von Walbeck, Deutschland, beschrieben. Das Exemplar ist ein gut erhaltener, unvollständiger rechter Tarsometatarsus und ist der früheste altweltliche Nachweis einer Eule. Von der gleichen Lokalität wird eine Praemaxilla beschrieben, die von einem ähnlich großen Raubvogel stammt und sich deutlich von der Praemaxilla aller heutigen Raubvögel unterscheidet. Obwohl es auch zu Berruornis gehören könnte, wird das Stück als Aves incertae sedis klassifiziert. Ungeachtet der Tatsache, daß das Fossilmaterial von Walbeck bereits vor mehr als 60 Jahren entdeckt wurde, sind diese beiden Exemplare die ersten Knochen, die von den zahlreichen an dieser Lokalität gefundenen Vogelresten bisher beschrieben wurden. doi:10.1002/mmng.20020050117